Recent Advances on Macrocyclic Trichothecenes, Their Bioactivities and Biosynthetic Pathway - Zhu, Muzi (Toxins (Basel), 2020)
Macrocyclic trichothecenes are an important group of trichothecenes bearing a large ring. Despite the fact that many of trichothecenes are of concern in agriculture, food contamination, health care and building protection, the macrocyclic ones are becoming the research hotspot because of their diversity in structure and biologic activity. Several researchers have declared that macrocyclic trichothecenes have great potential to be developed as antitumor agents, due to the plenty of their compounds and bioactivities. In this review we summarize the newly discovered macrocyclic trichothecenes and their bioactivities over the last decade, as well as identifications of genes tri17 and tri18 involved in the trichothecene biosynthesis and putative biosynthetic pathway. According to the search results in database and phylogenetic trees generated in the review, the species of the genera Podostroma and Monosporascus would probably be great sources for producing macrocyclic trichothecenes. Moreover, we propose that the macrocyclic trichothecene roridin E could be formed via acylation or esterification of the long side chain linked with C-4 to the hydroxyl group at C-15, and vice versa. More assays and evidences are needed to support this hypothesis, which would promote the verification of the proposed pathway.